2021
DOI: 10.3389/fncel.2021.648210
|View full text |Cite
|
Sign up to set email alerts
|

Control of Microbial Opsin Expression in Stem Cell Derived Cones for Improved Outcomes in Cell Therapy

Abstract: Human-induced pluripotent stem cell (hiPSC) derived organoids have become increasingly used systems allowing 3D-modeling of human organ development, and disease. They are also a reliable source of cells for transplantation in cell therapy and an excellent model to validate gene therapies. To make full use of these systems, a toolkit of genetic modification techniques is necessary to control their activity in line with the downstream application. We have previously described adeno-associated viruse (AAV) vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Organoids are organ-mimicking multicellular 3D structures. Retinal organoids have been utilized for optogenetic vision restoration in mice by Garita-Hernandez et al (2019 , 2021) . In their studies, human-induced pluripotent stem cells were differentiated into retinal organoids.…”
Section: Methods Aiding Optogenetics In Neurosciencementioning
confidence: 99%
“…Organoids are organ-mimicking multicellular 3D structures. Retinal organoids have been utilized for optogenetic vision restoration in mice by Garita-Hernandez et al (2019 , 2021) . In their studies, human-induced pluripotent stem cells were differentiated into retinal organoids.…”
Section: Methods Aiding Optogenetics In Neurosciencementioning
confidence: 99%
“…One intriguing approach to this conundrum is the use of optogenetically engineered hiPSC-PRP, which have recently been shown to generate modest responses to bright light in vitro and in vivo. 163 , 189 However, such a genetic modification presumes that hPSC-derived PRs cannot innately respond to light and also introduces aforementioned regulatory hurdles. In the absence of genetic modification of hPSC-PRP, other potency assays may prove useful for authenticating batches of transplantable hPSC-PRP, including examinations of cell polarity, synaptic marker expression, 190 PR marker expression, axon outgrowth, and membrane electrophysiology.…”
Section: Current Status and Remaining Questions For Retinal Cell Therapiesmentioning
confidence: 99%
“…A number of recent xenograft studies have demonstrated proof-of-concept for PR survival and anatomic engraftment (see Supplementary Note S1 ) following transplantation of dissociated hPSC-derived cell suspensions or retinal sheets in rodents 146 , 149 , 161 163 , 179 , 189 and non-human primates (NHPs), 147 , 160 using controls for biomaterial transfer. Dissociated cell injections have the advantage of being relatively simple, cost-effective, rapid, and minimally invasive, although graft organization and cell survival is often suboptimal.…”
Section: Current Status and Remaining Questions For Retinal Cell Therapiesmentioning
confidence: 99%
See 2 more Smart Citations